Determination of Total Flavonoid Content and Characterization of Nanoparticles of Kecombrang Leaf Extract (Etlingera elatior (Jack) R.M.Sm.) - Hayati, Farida; Sofi Nurmay Stiani; Renditya Ismiyati (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
Kecombrang (Etlingera elatior (Jack) R.M.Sm.) is one of Indonesia's potential plants that contain such bioactive compounds as polyphenols, alkaloids, flavonoids, steroids, saponins, and essential oils. This study aims to determine the total flavonoid content of kecombrang leaf extract. It also defines the characteristics of the nanoparticles of kecombrang leaf extract. Kecombrang leaves were extracted through maceration. The determination of the total flavonoid content by spectrophotometry used quercetin as a comparison. The synthesis of nanoparticles used ionic gelation with 0.1% sodium alginate and 0.01% calcium chloride crosslinkers. The characteristic parameters of the nanoparticles of kecombrang leaf extract included the visual, transmittance, adsorption efficiency, particle size distribution, polydispersity index, and zeta potential. The yield value was 46.55%. The total flavonoid content was 88.11 mgQE/g with a regression standard curve Y = 0.1022x + 0.0745 and correlation coefficient (r) = 0.9922. The nanoparticle solution provided a clear visual with a particle size and PI of 108.2 nm and 0.311, a transmittance and adsorption efficiency of 94.76% and 93.76%, and a zeta potential of -36 mV. The total flavonoid content was 88.11 mgQE/g. The nanoparticle solution of kecombrang leaf extract has the characteristics that qualify as a nanoparticle preparation.